Yoga Exercise Models for Flexibility - I Wayan Muliarta (Universitas Pendidikan Ganesha, 2023)
For now, the achievements of silat athletes cannot be said to be encouraging. There are still many athletes who still need a good physique. This study aimed to produce a yoga exercise model for flexibility. This type of research is adapted to the design of development research by Borg and Gall. The participants involved in this study were Pencak silat athletes, totaling 65. Observation, interviews, and questionnaires collected data. The stages of data collection were carried out in the early stages; expert tests, limited tests on small groups, field tests, and effectiveness tests using statistical methods. The study's results prove that the overall exercise model can be used and is in the pilot stage from the evaluation results of yoga experts and trainers. The small group trial stated that silat athletes could apply and practice the developed model. The large group trial stated that the exercise model developed helped increase the variety of flexibility exercises. Based on the model's effectiveness, there are differences in flexibility before and after implementing the yoga practice model. It was concluded that developing a yoga exercise model proved beneficial for increasing the variety of athletes' training and effectively increasing the flexibility of Pencak silat athletes.